2010
DOI: 10.1007/s00262-010-0890-5
|View full text |Cite
|
Sign up to set email alerts
|

Leukemic cell products down-regulate human dendritic cell differentiation

Abstract: The microenvironment produced by solid tumors is inhibitory to the immune system, inducing dendritic cell (DC) alterations, but there is a paucity of information regarding haematological malignances. The aim of this study was to investigate DC differentiation under the influence of leukemic cell products. Monocytes from healthy volunteers were cultured in the presence of IL-4 and GM-CSF for the generation of immature DCs. Supernatants from leukemic cultures were added to monocyte cultures during differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…It was recently shown that TEM-8 is upregulated in tumor-associated endothelial cells after exposure to interleukin-1β (IL-1β) [21]; interestingly, IL-1β, together with tumor necrosis factor-α (TNF-α) and other cytokines produced by tumor cells (melanoma included) [22], can negatively affect the differentiation of monocyte-derived DC in vitro [23]. As IL-1β and TNF-α are components of the cytokine maturation cocktail currently used to prepare the DC vaccine, it would not be surprising that, at least in a subset of patients, these cytokines support the differentiation of DC toward an immunosuppressive TEM-8 + phenotype rather than the more immunogenic and clinically active phenotype.…”
Section: Background and Rationalementioning
confidence: 99%
“…It was recently shown that TEM-8 is upregulated in tumor-associated endothelial cells after exposure to interleukin-1β (IL-1β) [21]; interestingly, IL-1β, together with tumor necrosis factor-α (TNF-α) and other cytokines produced by tumor cells (melanoma included) [22], can negatively affect the differentiation of monocyte-derived DC in vitro [23]. As IL-1β and TNF-α are components of the cytokine maturation cocktail currently used to prepare the DC vaccine, it would not be surprising that, at least in a subset of patients, these cytokines support the differentiation of DC toward an immunosuppressive TEM-8 + phenotype rather than the more immunogenic and clinically active phenotype.…”
Section: Background and Rationalementioning
confidence: 99%
“…immature DCs (Bharadwaj et al 2007;Motta et al 2010;Sallusto and Lanzavecchia 1994). The inhibition of DCs development may be a way to ensure tumour cell survival, as the immune response becomes compromised (Motta et al 2010). Indeed, it was found that IL-1b and PGE 2 produced by tumour cells inhibited the Mo differentiation into immature DCs (Motta et al 2010;Sombroek et al 2002).…”
Section: Morphology Phenotype and Cd83mentioning
confidence: 99%
“…DCs (Kalinski et al 1998). Although the aforementioned cytokines were capable of inducing DCs maturation, they inhibited DCs differentiation from Mo (Motta et al 2010;Sallusto and Lanzavecchia 1994;Sombroek et al 2002). Addition of TNF-a, IL-1b or IL-6 to Mo cultures prevented the loss of CD14 as well as the appearance of CD1a molecules, and hence suppressed the in vitro generation of CD14 -CD1a…”
Section: Morphology Phenotype and Cd83mentioning
confidence: 99%
See 2 more Smart Citations